Develop a remote control aircraft for crop spraying / Noor Shuhada Hussin - Hussin, Noor Shuhada (2004)
This is a report of our final year project title “Develop a Remote Control Aircraft for Crop Spraying”. This final project was supervised by Mrs. Wan Mazlina Wan Mohamed. Through this project, we are encouraged to find in detail about the Unmanned Aerial Vehicle (UAV) application on agriculture. We have to analyze how far the used of the UAV in agriculture sector at Malaysia. From the discussion with our advisor, Mrs. Wan Mazlina, we have to develop a prototype model of a sprayer that can be used either to spray fertilizer or pesticide by a remote control aircraft. We had to decide which type of the UAV that is suitable for this project whether it is fixed wing type or rotary wing. After we had developed the sprayer model, testing was conducted in order to make sure that the model can be function well. Then, we manage to measure the volume flow rate and the coverage besides to find the dimension of the model. Finally, there must be some recommendation to improve the prototype model. With that recommendation, we hope that it can be used as a guide to other students to build a better model in the future.